Pendampingan Pembelajaran Kosakata Bahasa Arab melalui Metode Drill Berbasis Game-Based Learning pada siswa kelas II SD Alif Rimba - Fazari Zul Hasmi Kanggas; Selmarisa Wardhani; Kemal Yudha Bimantoro; Siska Cholydia Harnum (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
This community service activity aimed to improve the Arabic vocabulary mastery of second-grade students at Alif Rimba Elementary School through the implementation of the Drill Method in the learning process. The Drill Method was selected because it is considered effective for foreign language instruction, particularly Arabic, as it helps students develop vocabulary memorization and comprehension skills through repetitive and structured practice. The activity was carried out in the form of Arabic language learning assistance involving second-grade students at Alif Rimba Elementary School. The implementation stages included needs identification, learning activities using the Drill Method, and evaluation through pre-tests and post-tests. The results demonstrated an improvement in students’ ability to memorize and understand Arabic vocabulary. This improvement was evidenced by the evaluation results, which showed an increase in the number of students who correctly answered the test questions in the post-test compared to the pre-test. Therefore, the Drill Method can serve as an effective alternative learning strategy for enhancing Arabic vocabulary mastery among elementary school students.